Spirituality-Based Accountability at Padepokan Eyang Djugo - Wahyuni, Dian Puspa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the management of religious organizations, the principles of accountability and trust from members of the organization play a very important role. However, there is a unique phenomenon from the religious organization of Padepokan Eyang Djugo, in which the principle of accountability used is not a conventional accountability principle that applies high control to every activity of the organization, but the basis of the management of the hermitage is belief in God and Grandmother Djugo. The two entities later transformed into a unifying Padepokan for decades.